Plan de negocios para la creación de una empresa de coworking tomando las mejores prácticas de Estados Unidos - Balarezo Alcívar, Gabriela Liseth (2019)
Those who believe in collaboration rather than competition, grow, learn and become people with competencies. The "coworking" or "collaborative work" is the perfect balance between the freedom to work alone and the wonderful thing of working in community; what it seeks is to provide spaces or work offices for those who want to develop their activities. The aforementioned, combined with the impact and environmental damage by many companies today, has awakened the initiative to help the contribution of having a better place to perform daily activities through the construction of a self-sustaining building in order to live in harmony with the environment while direct benefits are perceived as cost reduction and generation of networks of contacts with different industries, especially those "green". Thus, the present business plan, which takes the name "EcoWorking", seeks to propose a shared work model based on the best practices of companies in this industry in the United States, adapting them to the Ecuadorian market in order to evaluate their viability through several tools studied throughout the project. In this way, two segments are identified: natural persons: entrepreneurs, consultants and independent workers (freelancers); and legal persons: small business management companies, administrative and support services; it is quantitative and qualitative analysis distinguishes the needs that could be met. In addition, it takes into account the resources and real capacity of a company with these characteristics for the creation of the organizational structure and the marketing plan with its product, price, place and promotion strategies, which defines the essential characteristics of the project. Finally, the initial investment needed to start operating is high and has an amount of $803,189.42, where 60% will be financed by a 5-year bank and 40% will be owned by two partners. The last chapter presents the results of the financial analysis.